Preparation of Antimicrobial Hyaluronic Acid/Quaternized Chitosan Hydrogels for the Promotion of Seawater-Immersion Wound Healing - Wang, Xinlu; Xu, Pengcheng; Yao, Zexin; Fang, Qi; Feng, Longbao; Guo, Rui; Cheng, Biao (Frontiers in Bioengineering and Biotechnology, 2019)
Wound immersion in seawater with high salt, high sodium, and a high abundance of pathogenic bacteria, especially gram-negative bacteria, can cause serious infections and difficulties in wound repair. The present study aimed to prepare a composite hydrogel composed of hyaluronic acid (HA) and quaternized chitosan (QCS) that may promote wound healing of seawater-immersed wounds and prevent bacterial infection. Based on dynamic Schiff base linkage, hydrogel was prepared by mixing oxidized hyaluronic acid (OHA) and hyaluronic acid-hydrazide (HA-ADH) under physiological conditions. With the addition of quaternized chitosan, oxidized hyaluronic acid/hyaluronic acid-hydrazide/quaternized chitosan (OHA/HA-ADH/O-HACC and OHA/HA-ADH/N-HACC) composite hydrogels with good swelling properties and mechanical properties, appropriate water vapor transmission rates (WVTR), and excellent stability were prepared. The biocompatibility of the hydrogels was demonstrated by in vitro fibroblast L929 cell culture study. The results of in vitro and in vivo studies revealed that the prepared antibacterial hydrogels could largely inhibit bacterial growth. The in vivo study further demonstrated that the antibacterial hydrogels exhibited high repair efficiencies in a seawater-immersed wound defect model. In addition, the antibacterial hydrogels decreased pro-inflammatory factors (TNF-α, IL-1β, and IL-6) but enhanced anti-inflammatory factors (TGF-β1) in wound. This work indicates that the prepared antibacterial composite hydrogels have great potential in chronic wound healing applications, such as severe wound cure and treatment of open trauma infections.